Across the borders financing the world's railways in the nineteenth and twentieth centuries (Modern economic and social history series, 2008)
This volume provides a wide introduction to how financiers, governments and entrepreneurs in Europe managed to face the challenges of constructing and maintaining an integrated railway network, both in their own countries and their colonies.